Ethnoecology and ethnomedicinal use of fish among the Bakwele of southeastern Cameroon - Takanori Oishi (Revue d'ethnoécologie)
Ethnoichthyology is a branch of ethnobiology that explores the relationships between humans and fish, including local ecological knowledge about ichtyofauna, capture processes and utilization of the catches. Because of the current bushmeat trade crisis, the aquatic resources in the Congo Basin rainforest are increasingly viewed has promising alternate resources and have recently drawn the attention of conservation and development agencies. Yet, more attention should be given to the social context of fishing and to the cultural values locally attributed to fish. This paper describes some aspects of the ethnoichthyology of the Bakwele, a group of shifting cultivators of southeastern Cameroon. While focusing on the local ecological knowledge and the medicinal uses of fish by the Bakwele, the paper aims to emphasize the ecological and sociocultural interactions that form the basis of their art of fishing.